2022
DOI: 10.3389/fphar.2022.864509
|View full text |Cite
|
Sign up to set email alerts
|

A Process for the Design and Development of Novel Bone Morphogenetic Protein-7 (BMP-7) Mimetics With an Example: THR-184

Abstract: Growth Factors have been evaluated as therapeutic targets for the treatment of a broad spectrum of diseases. Because they are proteins with pleiotropic effects, the quest to harness their beneficial effects has presented challenges. Most Growth Factors operate at the extracellular-receptor level and have natural feedback mechanisms that modulate their effects. As proteins, they are difficult and expensive to manufacture. Frequently proteins must be administered parenterally, may invoke an immune response, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 121 publications
0
9
0
Order By: Relevance
“…Disruptions in the excitation–inhibition balance and homeostatic adaptations have been implicated in neurodevelopmental disorders, and reduced GABAergic signalling and a propensity to develop epilepsy are often seen in individuals with autism 3 5 , 52 . Considering that BMP signalling pathways can be targeted with peptide mimetics 53 , these might provide an entry point for therapeutic interventions in neurodevelopmental disorders that are characterized by disruptions in the innervation of PV interneurons, the excitation–inhibition balance and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions in the excitation–inhibition balance and homeostatic adaptations have been implicated in neurodevelopmental disorders, and reduced GABAergic signalling and a propensity to develop epilepsy are often seen in individuals with autism 3 5 , 52 . Considering that BMP signalling pathways can be targeted with peptide mimetics 53 , these might provide an entry point for therapeutic interventions in neurodevelopmental disorders that are characterized by disruptions in the innervation of PV interneurons, the excitation–inhibition balance and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions in excitation -inhibition balance and homeostatic adaptations have been implicated in neurodevelopmental disorders as there is reduced GABAergic signaling and a propensity to develop epilepsy in individuals with autism [49][50][51]54 . Considering that BMPsignaling pathways can be targeted with peptide mimetics 55…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions in excitation – inhibition balance and homeostatic adaptations have been implicated in neurodevelopmental disorders as there is reduced GABAergic signaling and a propensity to develop epilepsy in individuals with autism 5456,59 . Considering that BMP-signaling pathways can be targeted with peptide mimetics 60 they may provide an entry point for therapeutic interventions in neurodevelopmental disorders characterized by disruptions in PV interneuron innervation, excitation – inhibition balance, and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…These are exclusively represented by protein or peptide modalities, which are beyond the scope of this Review. To provide a brief overview, a variety of BMP mimetic peptides were designed based on crystal structures of BMPs or BMP receptors. Notably, THR-184 was tested in phase 1 and phase 2 clinical trials for the prevention of cardio­vascular-associated acute kidney injury, where it demonstrated safety but no significant efficacy. , “BMP activators” also act on the receptor level; they do not mimic ligands but rather enhance the activation of downstream signaling effectors. As the largest and most diverse set, we categorized “BMP potentiators” that increase cellular responsiveness to BMP, typically dependent on at least low-level basal pathway activity.…”
Section: Bmp Stimulatorsmentioning
confidence: 99%
“…90−93 Notably, THR-184 was tested in phase 1 and phase 2 clinical trials for the prevention of cardiovascular-associated acute kidney injury, where it demonstrated safety but no significant efficacy. 90,94 "BMP activators" also act on the receptor level; they do not mimic ligands but rather enhance the activation of downstream signaling effectors. As the largest and most diverse set, we categorized "BMP potentiators" that increase cellular responsiveness to BMP, typically dependent on at least low-level basal pathway activity.…”
Section: Bmp Stimulatorsmentioning
confidence: 99%